ENGLISH INFLUENCE ON THE UZBEK LEXICON: A SOCIOLINGUISTIC STUDY OF BORROWING, ADAPTATION, AND IDENTITY - Aytmuxamedova Durdona Jasur qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
The Uzbek language, like many others in the globalized world, is undergoing significant lexical transformation under the influence of English. This paper investigates the nature, causes, and sociolinguistic implications of English borrowings in Uzbek, focusing on how these borrowings reflect broader processes of cultural contact and identity negotiation. The study argues that lexical borrowing is not merely a linguistic phenomenon but a socio-cultural response to globalization, modernization, and technological advancement. Drawing upon theories of language contact and sociolinguistics, this paper explores the adaptation mechanisms of English words in Uzbek, the social factors motivating borrowing, and the cultural meanings attached to such linguistic shifts. Ultimately, it demonstrates that English lexical influence on Uzbek reveals a complex interaction between linguistic innovation, social aspiration, and national identity.